Relationship of Problematic Smartphone Use, Sleep Quality, and Daytime Fatigue Among Quarantined Medical Students During the COVID-19 Pandemic - Zhang, Chi; Zeng, Ping; Tan, Joshua; Sun, Siwei; Zhao, Minghao; Cui, Ju; Zhang, Guifang; Jia, Jinzhong; Liu, Deping (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic brought great transformation to medical education mode. Although mobile communication devices played a crucial role in online learning among quarantined university students, the potential smartphone addiction issue and related behaviors and psychological symptoms have not been recognized. This study examined the relationship between problematic smartphone use (PSU), sleep quality, and daytime fatigue among quarantined medical students. Methods: An online survey was conducted in six polyclinic hospitals in Beijing between February and May 2020. 1016 participants (26.01±2.46 years, 65.16% female) completed self-report measurements including Short Version Smartphone Addiction Scale (SAS-SV), Athens Insomnia Scale (AIS), and Subjective Fatigue Scale (FS). Spearman correlation coefficients and multiple regression models were used to analyze the association between PSU, quality, and daytime fatigue. We used structural equation modeling to test the mediating effect of sleep disturbance between PSU and daytime fatigue. Results: 48.62% of the participants had PSU. Significant positive correlations were found between SAS-SV, AIS, and FS scores (r=0.35-0.61, PS<0.001). Subjects with PSU were more likely to report sleep disturbance (β=1.07, P<0.001, OR=2.91, 95%CI=2.17-3.91), physical fatigue (β=1.16, P<0.001, OR=3.18, 95%CI=2.45-4.15), and mental fatigue (β=0.88, P<0.001, OR=2.42, 95%CI=1.86-3.14). We obtained a partial mediating effect model with sufficient fitness (χ2/df =2.25, P=0.133, CFI=0.99, NFI=0.99, and RMSEA=0.03). The indirect effect of PSU on daytime fatigue mediated by sleep disturbance accounted for 51.06% of the total effect. Conclusions: PSU was significantly associated with sleep disturbance and fatigue among medical students during the COVID-19 pandemic. Sleep quality mediated the relationship between PSU and daytime fatigue. Our results provide valuable information for maintaining students’ health status and constructing online education structures in countries suffering pandemics.